Batch Foaming of Amorphous Poly (DL-Lactic Acid) and Poly (Lactic Acid-co-Glycolic Acid) with Supercritical Carbon Dioxide: CO2 Solubility, Intermolecular Interaction, Rheology and Morphology - Tai, Hongyun (IntechOpen, 2012)
None